ANALISA DAN PERANCANGAN LOAD BALANCING PADA WARNET DENGAN KONEKSI 2 ISP - Kurniabudi - (JURNAL AKADEMIKA)
The convenience of internet access is a very important thing to be noted by the maintainer of cybercafes. The Cafe will be abandoned if customers are not able to provide an internet connection with sufficient bandwidth and provides the connection that is stable. Most cybercafe subscribed internet connection more than 1 (one) ISP as the backup path if the path is another ISP connection is down. With 2 (two) ISP connection needed efforts to set up load balancing burden on both lines so as to provide a stable internet connection. Load balancing is the most widely used method is to divide the load connection with 2 (two) connections. Discussion in this study include load balancing system on 2 (two) line connection ISP internet connection problems, analyze the internet connection problems in cybercafe, designing the system load balancing for 2 (two) internet connection and implement load balancing system on the PC the router.